Central airway obstruction tumour debulking using rigid bronchoscopy and cryotherapy: A case report - Chew W.H.; Marwan A.Z.; Daut U.N.; Ismail R.; Nasaruddin M.Z.; Rahman J.A.A. (Universiti Putra Malaysia Press, 2024)
Indexed by Scopus/MyCite